Kajian Semantik Denotasi dan Konotasi dalam Bahasa Arab: Pendekatan Analisis Tematik - Thayyibah, Uyun; Susiawati, Wati (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeru Sultan Aji Muhammad Idris Samarinda, 2025)
In studying the science of meaning or semantics (dalalah science) there are many kinds of meaning, two of which are denotation meaning and connotation meaning. In Arabic, denotation and connotation meanings are not only limited to one dimension as in Indonesian. Therefore, the purpose of this study is to find out the meanings in Arabic that are commensurate with denotation and connotation meanings. This research is a library research with a descriptive qualitative approach. The data collection method uses library techniques. And using thematic analysis techniques, namely identifying themes related to denotative meaning and connotative meaning of Arabic contained in books, books, and scientific journals. Because there is no literature that provides an explicit classification of the meaning of denotative and connotative equivalents in Arabic, this paper will contribute to providing an understanding of the differences in denotative and connotative meanings in Arabic. The three equivalent meanings are: the first is the basic meaning and the Idafi meaning, the second is the haqiqi meaning and the majazi meaning, the third is the mukjami meaning and the siyaqi meaning. The three meanings have a relationship or connection with each other.